Rising to the Challenge How to Develop Responsible Leaders - Wilson, Andrew; Wilson, Andrew (Center for Creative Leadership, 2007)
Today's companies recognize that they are actors in large, complex systems and that they need to interact in a web of relations with various groups of stakeholders. In particular, businesses are facing increasing pressures to make a positive contribution to society beyond the traditional economic benefits that derive from corporate activities. However, many organizations are struggling to define and develop the leadership skills and abilities necessary to translate the principles of corporate social responsibility into practice. A new study provides some clarity.